RESPIRATORY GYMNASTICS AS A REHABILITATION MEANS FOR THE PRESCHOOL CHILDREN WITH THE RESPIRATORY PATHOLOGY - T.A. Shemyakina; E.V. Golikova; E.I. Kondrat'eva; Ya.A. Plachkova; N.P. Stepanenko ("Paediatrician" Publishers LLC, 2007)
The researchers analyzed the efficacy of the new medical technology aimed at rehabilitation of the preschool children with the respiratory pathology. 177 children aged between 2 and 7 with recurrent respiratory diseases, bronchial asthma or chronic pathology of the end organs have been examined for 9 months. It was uncovered that among children (n = 90), who performed the sets of the therapeutic physical training and respiratory gymnastics according to the methods developed by the authors, the recurrence of the acute respiratory diseases and exacerbations of bronchial asthma was lower by 1,83 and 1,86 timers respectively. Besides, among children of this group the researchers noted the significant improvement of the physical qualities, spirometric indices and cytological picture of the substance removed from the nasal cavity if compared with the children from the screening group (n = 87), who performed the sets of the conventional gymnastics at the physical training lessons. Thus, the researchers proved the high efficacy of the proposed technology for the rehabilitation of the children, suffering from the chronic respiratory pathology. Key words: acute respiratory diseases, asthma, therapeutic physical training, respiratory gymnastics, children.